Implementasi Konsep Madrasah Berwawasan Lingkungan (Studi Kasus di MAN Purworejo) - Nur Chamidah (LPPM IAINU Kebumen, 2020)
This study aims to describe the Adiwiyata School at MAN Purworejo which includes 4 components of the Adiwiyata program, namely environmentally sound policies, Implementation of Environment-Based Curriculum, Participatory-Based Environmental Activities and Management of Environmentally Friendly Support Facilities. This research is a qualitative research with a descriptive approach. The informants for this research were the School Adiwiyata Team, the Principal, Deputy Principal for Facilities and Infrastructure, School Public Relations, Teachers, Employees and Students. Research location at MAN Purworejo Data collection techniques with triangulation through interviews, observation, and documentation studies. The results of the study show that: (1) the implementation of environmentally sound policies has been carried out by changing the vision and mission to support environmental management and there is an allocation of funds for the Adiwiyata program in efforts to protect and manage the school environment, an environmentally sound curriculum is implemented by integrating environmental insight material into subjects , participatory environmental activities are carried out through various environmental actions both held by schools and agencies and managing environmentally friendly facilities by utilizing Green Houses, green open spaces and school yards for learning. (2) Schools have attempted several activities involving students in the Adiwiyata program, including involving students in environmental actions, and environmental workshops and waste recycling training. The obstacles faced were the lack of cooperation and the lack of awareness of students regarding madrasa concerns.